Highly scalable intelligent sensory application and time domain matrix for safety-critical system design - Taikyeong Ted Jeong (International Journal of Distributed Sensor Networks)
The designs of highly scalable intelligent sensory application—Ethernet-based communication architectures—are moving toward the integration of a fault recovery and fault-detection algorithm on the automotive industry. In particular, each port on the same network interface card design is required to provide highly scalable and low-latency communication. In this article, we present a study of intelligent sensory application for the Ethernet-based communication architecture and performance of multi-port configuration which is mainly used in safety-enhanced application such as automotive, military, finance, and aerospace, in other words, safety-critical applications. Our contributions and observations on the highly scalable intelligent behavior: (1) proposed network interface card board design scheme and architecture with multi-port configuration are a stable network configuration; (2) timing matrix is defined for fault detection and recovery time; (3) experimental and related verification methods by cyclic redundancy check between client–server and testing platform provide comparable results to each port configurations; and (4) application program interface–level algorithm is defined to make network interface card ready for fault detection.